2017
DOI: 10.1158/1078-0432.ccr-16-1300
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Genome Editing to Generate Universal CAR T Cells Resistant to PD1 Inhibition

Abstract: Purpose Using gene-disrupted allogeneic T cells as universal effector cells provides an alternative to and potentially improves current chimeric antigen receptor (CAR) T cell therapy against cancers and infectious diseases. Experimental Design The CRISPR/Cas9 system has recently emerged as a simple and efficient way for multiplex genome engineering. By combining the lentiviral delivery of CAR and CRISPR RNA electroporation to co-introduce RNA encoding the Cas9 and gRNAs targeting endogenous TCR, beta-2 micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
652
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 765 publications
(699 citation statements)
references
References 42 publications
11
652
0
Order By: Relevance
“…Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade. Genomic editing of chimeric antigen receptor (CAR) T cells to render them resistant to exhaustion has been proposed 63,64 , and Sen and colleagues suggested that mapping state-specific enhancers in exhausted T cells could enable more precise genome editing for adoptive T cell therapy 62 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Epigenetic and transcriptional mechanisms determine the functional plasticity of T cells to switch between their exhausted and effector states 62 , and so altering the transcriptional landscape-for example, by manipulating transcription-factor and gene-enhancer expression-and epigenetic landscape-for example, by manipulating the activity of histone-modifying methylation or demethylation enzymes, histone acetylases, and DNA demethylases-of adoptively transferred T cells may yield a more specific anti-tumor response than generalized PD-1 and CTLA-4 blockade. Genomic editing of chimeric antigen receptor (CAR) T cells to render them resistant to exhaustion has been proposed 63,64 , and Sen and colleagues suggested that mapping state-specific enhancers in exhausted T cells could enable more precise genome editing for adoptive T cell therapy 62 .…”
Section: Autoimmune Consequencesmentioning
confidence: 99%
“…Genome editing to create CAR T cells or TCR transgenic T cells devoid of the endogenous TCR in order to prevent GVHD and enhance the function of the transgenic TCR has been reported 64,100,101 .…”
Section: Box 1 Adoptive T Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these findings underline the need to define which subpopulation of TILs expresses PD-1 and whether and to which extent PD-1 expression reflects activation or inhibition. Finally, we are encouraged to support PD-1-to-CD8 ratio as a potential biomarker by the first approved clinical trial applying the CRISPRcas technology in lung cancer, in which PD-1 inhibitory receptor has been genetically disrupted in adoptive cell transfer (43).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular repair at such sites by Non Homologous End Joining (NHEJ) creates a variety of insertions and deletions (Indels), disrupting native sequences and, depending on the target site, resulting in defective or absent gene expression. The addition of Clustered regularly interspaced short palindromic repeat (CRISPR)-Cas9 reagents to the editing toolbox has further extended the range of genomic sites susceptible to DNA scission [15][16][17]. Improvements in the ability to deliver editing reagents into cells as RNA have been a key advance that has allowed translation and scalability to therapeutic strategies.…”
mentioning
confidence: 99%